Improved numerical analysis of structures reinforced by composite FRP: Hygrothermal and prestressing loads with taper effect. (19th June 2019) - Hebbaz, Mohammed Amine; Kerboua, Bachir; Tarfaoui, Mostapha
Fiber-reinforced polymer (FRP) composites are becoming suitable and substantial materials in repairing and replacing conventional metallic materials because of their high strength and stiffness. Steel beams can be strengthened in flexure using bonded FRP or using steel plates. In such plated beams, shear forces develop in the bonded beam and these will be transferred to the FRP plate via the adhesion technique. Thus, the interfacial shear stress and normal stress will develop consequently, and debonding may occur at the FRP plate ends due to high interfacial stress values in this area. This original research aims to study the debonding phenomenon using an analytical and a numerical finite element models, in order to identify the interfacial stresses of a steel beam strengthened by the FRP plate with taper model, taking into account a new coupled approach of prestressing force and hygrothermal effect. This article explores the effects of various parameters, such as geometrical and physical properties, on the stress behavior of FRP composites.